Neuroscientific Discoveries and Their Implications for Early Childhood Language Education - Khakimova, Mukhabbat; Jakhongir, Shaturaev; Fayzullayeva, Nilyufar; Mamarajabov, Shavkat; Ochilova, Gulnoza; Musakhanova, Gulnora; Pantin, Roman; Akbarova, Sayyora; Kayumova, Mekhribonu; Khojiyeva, Iroda (Forum for Linguistic Studies, 2025)
Recent advancements in neuroscience have provided valuable insights into how the brain functions, offering significant potential for enhancing educational practices. Despite this, current neuroscientific findings on how the brain learns - particularly in early childhood language acquisition - are not fully utilized in educational settings. This article investigates the foundational principles of educational neuroscience as an interdisciplinary field, situated at the intersection of neurobiology, pedagogy, and cognitive science. It emphasizes the integration of neuroscientific research into educational practices, specifically focusing on language development during early childhood and assessing the reciprocal influence of education on brain function. The paper traces the origins and progress of neuroscience in education while addressing the terminological ambiguity in modern scientific literature concerning the relationship between neuroscience and education. It also highlights promising pathways for collaboration among psychology, pedagogy, and neuroscience, with special attention to early language learning. A scientometric analysis of key research trends in the neuroscience-education nexus, based on the Scopus scientific literature database, is presented. This study seeks to enhance the dialogue between neuroscientific discoveries and educational applications, advocating for a more integrated approach to improve learning outcomes. It underscores the necessity of interdisciplinary collaboration to bridge the gap between theoretical insights from neuroscience and the practical needs of educational environments, particularly in fostering early childhood language development.